Textbook of surgery pocket companion - Sabiston, David C. (W.B. Saunders, 1997)
This pocket-sized resource provides convenient, portable access to all of the procedures and techniques covered in TEXTBOOK OF SURGERY, 15th Edition. Concentrates on the specific how-to's of the surgical operations, and includes information on the anatomical, pathological, physiological, biochemical, molecular, and biological basis of each subject.